Keterampilan komunikasi ibu dan perkembangan personal-sosial anak prasekolah: Studi kasus di TK Taruna Karya, Kecamatan Bontobahari - Basri; Ilyas, Halmina; Suras, Andi Ainul; Sulaiman (EcoVision: Journal of Environmental Solutions, 2024)
Background: According to 2020 data from the Central Statistics Agency, there are approximately 30.83 million early childhood children, with 29.28% of them being preschool-aged (5-6 years old). At the preschool stage, children's personal-social development is influenced by various factors, including communication, the surrounding environment, health status, and peer interactions. A friendly/effective communication model between a mother and her child plays a crucial role in creating the home as the child's first/primary social environment. Effective communication can help improve children's personal-social skills, which are essential for healthy social interactions outside the home. This study aims to explore the correlation between mothers' communication skills and the personal-social development of preschool children at TK Taruna Karya, Bontobahari District. Method: This study employs a quantitative approach with a cross-sectional design. The study population consists of mothers of 80 students from TK Taruna Karya, Bontobahari District. The sampling technique used is total/consecutive sampling, where all mothers of students in this population are included as samples. Data were collected using a questionnaire designed to evaluate mothers' communication skills and the personal-social development of their children. The data were then analyzed using SPSS 16 with a chi-square test and an alternative Fisher’s Exact Test to determine if there was a significant relationship between the studied variables. Findings: The analysis results showed a ρ-value of 0.000 (ρ<α=0.05), indicating a significant relationship between mothers' communication skills and the personal-social development of preschool children at TK Taruna Karya. Conclusion: This study concludes that there is a significant relationship between mothers' communication skills and the personal-social development of preschool children at TK Taruna Karya, Bontobahari District. Improved mothers' communication skills contribute positively to the personal-social development of a child.